THE ROLE OF TRANSPORT COMMUNICATIONS IN STRENGTHENING INTERSTATE ECONOMIC COOPERATION BETWEEN UZBEKISTAN AND IRAN - Temirbek Kuchkarov (International Journal of Literature and Language Studies, 2026)
Transport communications occupy a system-forming place in the economic relations between Uzbekistan and Iran. As a double-landlocked state, Uzbekistan depends on stable, diversified, and cost-efficient transit routes for access to external markets, whereas Iran offers outlets to the Persian Gulf and the Gulf of Oman - including the ports of Bandar Abbas and Chabahar - and serves as a bridge toward India, the Middle East, Turkey, and Europe. Drawing on recent intergovernmental agreements, corridor initiatives, and analytical studies, this article argues that transport links are evolving from an auxiliary sector into a strategic instrument of trade growth, logistics diversification, industrial cooperation, and broader regional integration. The findings show that the greatest economic gains arise when infrastructure, institutions, and corridor integration advance together.